Supply response of wheat and barley in Iraq - Gawad, Taleb Ali (2014)
Iraq's agricultural sector employs more than 30% of the population and it is the main source of food for the population as well as animal feed. It also provides raw material for processing for many industries in Iraq. Wheat and barley can be considered as the most important major cereal crops in Iraq and the world for being the main food crops for the majority of the world's population, and its strong strategic relationship to food security. In Iraq, cereal production has been marked by fluctuations during 1980-2011 with an average annual production of 2,364 thousand tons, ranging from the highest production of 2,586 thousand tons in 2002 and the lowest production of 1,099 thousand tons in 1984. This fluctuation in production is due to several different reasons, including water scarcity, low rainfall, and not encouraging pricing policies and because of political circumstances. All these variables caused the reducing in the production of many crops, especially wheat and barley production in Iraq. Many variables affect the supply response on crops, the majority of the researchers usually focused on price and non-price variables, but they had not specified the kind of the irrigation. It can be clearly seen in this study was specified the kinds of irrigation for two kinds of irrigation firstly the irrigation by the river and secondly the irrigation by the rainfall, as well as the auto-regressive distributed lag Model (ARDL), Bounds testing approach to Co integration and the error correction model applied in this studythe auto regressive distributed lag (ARDL)model(Pesaran, Shin, & Smith, 2001). Production of wheat and barley was represented the dependent variable and the cultivated area, irrigation and crop price was represented the independent variables (explanatory variables). The unit root test was applied to understand these variables were stationary or not stationary by the ADF (Augmented Dickey-Fuller test).From ARDL, the F-statistic was used to test for Co integration between the variables. The long-run and the short-run relationship between the variables were then identified. Results indicated that barley area and its determinants; the relative price of wheat is Co integrated. The results also indicated that barley acreage is responsive to domestic price. This implies that price can be used as instruments to maintain favourable planted area. The result of production for barley irrigated by river (PRIB) and rain (PRAB) with an F-statistic of 11.9 and 12.03 respectively, and significant at 1 %. For wheat crop the F-statistic7.09 and 9.67 respectively. That implies that there is Co integration between the variables. For long-run and short-run periods, there is a significant effect for cultivation area and irrigation on the production while price also has a significant effect on the production in the long run. In conclusion, cultivation area, irrigation and crop prices have significant impacts on the production in the long run. Thus, the government should introduce policies which have significant impact on production by using a new system of irrigation and use new technology to extend the area planted and at the same time create a price policy to increase the production of wheat and barley.